The relationship between age and parity of pregnant women with the incidence of disrupted ectopic pregnancy at Wangaya hospital - Pemaron, Ida Bagus M.; Bandem, I. Ketut M. P.; Seputra, Dewa Ketut A. (International Journal of Advances in Medicine, 2022)
Background: Ectopic pregnancy is a phenomenon in pregnancy where after being fertilized, the egg cell implants and grows in the outer area of the endometrium of the uterine cavity. All ectopic pregnancies are at risk for spontaneously ruptured ectopic pregnancies. The incidence of ectopic pregnancy in the world is 0.25-2.0% of all pregnancies. In Indonesia, cases of ectopic pregnancy range from 5-6 per thousand pregnancies. One of the factors that influence the incidence of disrupted ectopic pregnancy is the age of the pregnant woman. Methods: A cross-sectional study was conducted at Wangaya regional general hospital in Denpasar among pregnant women with ruptured ectopic pregnancies between 2021 and 2022. Results: Based on the age category, the incidence of disrupted ectopic pregnancy was most common in the age range of 20-35 years old. Based on the parity category, the incidence of disrupted ectopic pregnancy was most common in the multigravida category. Conclusions: Based on age category, the incidence of disrupted ectopic pregnancy in Wangaya regional general Hospital in 2021-2022 mostly occurs at the age of 20-35 years, and based on the parity category of pregnant women, it is most common in multi gravida, which is found to be 65% of the total 40 cases.